Whitehorse Rapids on the Yukon River, Yukon Territory, 1899. - Barley, H. C.
Caption on image: "White Horse Rapids" PH Coll 246.121 [Meed journal: "White Horse Rapids. The stream flows to the left." To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number